"We`re not the same": A composite vignette on pregnancy and motherhood for elite athlete mothers in and out of funding programmes - Massey, K.; Whitehead, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction: Today, pregnancy is often viewed as a temporary phase allowing a break from the physical and mental pressures of high-performance sport rather than career closure. Yet, obtaining the elite athlete mother identity is not without struggle. A cultural shift sees sporting organisations developing contracts and policies to support the success of the post-partum return. Although there is much research on elite athlete mothers within professional contracts or in receipt of funding it has yet to explore how experiences differ between elite athlete mothers with and without these financial agreements. The present study aims to provide insight into the disparity between support of elite athletes with and without National Governing Body funding in hopes of informing future policy, provisions and practices for those elite athlete mothers who fall short of funding.